A second species of Dachibangus (Hemiptera: Fulgoromorpha: Mimarachnidae) in mid-Cretaceous amber from northern Myanmar. (November 2019) - Fu, Yanzhe; Szwedo, Jacek; Azar, Dany; Huang, Diying
Abstract: A fourth species of the mimarachnid planthoppers and a second species of Dachibangus is described and illustrated base on a well-preserved forewing in mid-Cretaceous amber of northern Myanmar. Dachibangus formosus sp. nov. can be distinguished from the type species Dachibangus trimaculatus Jiang, Szwedo et Wang, 2018 by the size of tegmen and its venation characters. Diagnostic features of the genus Dachibangus are reviewed. The new discovery further increases the documented palaeodiversity and morphological diversification of the Cretaceous mimarachnids.